2000
DOI: 10.1136/ard.59.12.945
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the synovial histology in rheumatoid arthritis, spondyloarthropathy, and osteoarthritis: influence of disease duration and activity

Abstract: Objectives-To compare the macroscopic and microscopic characteristics of synovial tissue in rheumatoid arthritis (RA), spondyloarthropathy (SpA), and osteoarthritis (OA) after exclusion of possible biases induced by disease duration or activity, or both. Methods-Synovial biopsy specimens were obtained by needle arthroscopy in patients with early RA (n=16), late RA (n=14), early SpA (n=23), and OA (n=12). Macroscopic and microscopic features were scored on a four point scale and analysed as a function of diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
195
1
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(215 citation statements)
references
References 46 publications
14
195
1
5
Order By: Relevance
“…Previously we demonstrated that HC gp-39 is not expressed exclusively in articular cartilage but is found also in inflamed synovium and that the synovial membrane is a privileged site for presentation of this protein to the immune system (6,14,19). In immunohistochemistry analyses for MIA in the present study, collected biopsies described previously (14,19,29,33) were used to investigate local expression of MIA in the synovium, with mAb 14A.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Previously we demonstrated that HC gp-39 is not expressed exclusively in articular cartilage but is found also in inflamed synovium and that the synovial membrane is a privileged site for presentation of this protein to the immune system (6,14,19). In immunohistochemistry analyses for MIA in the present study, collected biopsies described previously (14,19,29,33) were used to investigate local expression of MIA in the synovium, with mAb 14A.…”
Section: Resultsmentioning
confidence: 69%
“…Additional SF samples from RA, SpA, and osteoarthritis (OA) patients originated from a previous study (28). Synovial membrane biopsy specimens from another group of patients (described in previous reports [14,19,29]) were obtained for immunohistochemistry studies. Eight biopsy samples per patient (17 RA, 13 SpA, 6 OA), obtained from an inflamed knee joint by needle arthroscopy (30), were studied.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synovial tissue biopsy samples were processed and evaluated for lining layer thickness, vascularity, global inflammatory infiltration, and lymphoid aggregates, as described previously (35)(36)(37). Synovial tissues from the 158 RA patients were divided into 2 groups.…”
Section: Methodsmentioning
confidence: 99%
“…Dominique Baeten, 1 Elli Kruithof, 2 Maxime Breban, 3 and Paul P. Tak Spondylarthritis (SpA) is a major form of chronic inflammatory arthritis affecting both the peripheral joints and the axial skeleton. Despite clear differences in genetic background, demographic distribution, and pattern of joint inflammation between SpA and rheumatoid arthritis (RA), many of the drugs and strategies for the treatment of SpA have been translated from the RA field.…”
Section: Spondylarthritis In the Absence Of B Lymphocytesmentioning
confidence: 99%